(untitled) (Vietnam Journal of Community Medicine, 2021)
The cross-sectional descriptive study was conducted in 04 months, using quantitative data combined with qualitative information. Quantitative data was collected using a non-participating observation method, using a checklist. We observed 498 opportunities to wash hands. Qualitative information was collected from 02 in- depth interviews with experts and 03 group discussions. Data were entered and analyzed by Exel, Epidata and SPSS 18 software. The rate of compliance of nurses was 78.1. The chance of doing the right thing and completing the 6 steps is 71.9%. Practice of routine hand hygiene of nursing varies with working time, the highest was in the morning shift, lowest was evening shift. Factors that positively influenced the compliance are management and attention of the hospital leaders and the Department of Infection controls, regulations, circulars, training documents and guidelines; there is regular inspection and supervision and post-supervision feedback. Factors that adversely affect routine hand hygiene compliance are work overload, provision of unsanitary hand washing water and wash basins; the hospital has no regulations on specific rewards and penalties.